Does the Nominal Exchange Rate Explain the Backus-Smith Puzzle? Evidence from the Eurozone - M. Hadzi-Vaskov (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2007)
The negative correlation between relative consumption growth and real exchange rate changes is a recurrent puzzle in international macroeconomics (Backus and Smith, 1993). Using panel dataset with quarterly observations for all 12 countries from the Eurozone after the introduction of the common currency (1999-2006), this paper demonstrates that the nominal exchange rate is the main source of the puzzle. When nominal exchange rates fluctuations are eliminated, relative consumption growth is positively correlated with the change in the real exchange rate. Moreover, this result is contrasted with alternative samples of (relatively) flexible exchange rate: while the inflation differential is still positively correlated, the nominal exchange rate is negatively correlated with the relative consumption growth. These findings are robust to alternative regression specifications, estimation methods, and data samples.
Keywords: 330; International Risk-Sharing; Exchange Rates; Backus-Smith Puzzle